2020
DOI: 10.1021/jacs.9b11169
|View full text |Cite
|
Sign up to set email alerts
|

Versatile, Aqueous Soluble C2N Quantum Dots with Enriched Active Edges and Oxygenated Groups

Abstract: C2N has emerged as a new family of promising two-dimensional (2D) layered frameworks in both fundamental studies and potential applications. Transforming bulk C2N into zero-dimensional quantum dots (QDs) could induce unique quantum confinement and edge effects that produce improved or new properties. Despite their appealing potential, C2NQDs remain unexplored, and their intriguing properties and a fundamental understanding of their prominent edge effects are still not well understood. Here, we report the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 62 publications
(156 reference statements)
3
38
0
Order By: Relevance
“…These results indicated that the oxygenated edges enriched in the C 2 NQDs significantly improved the polysulfide immobilization and catalytic conversion. [ 111 ]…”
Section: C2n Applicationsmentioning
confidence: 99%
“…These results indicated that the oxygenated edges enriched in the C 2 NQDs significantly improved the polysulfide immobilization and catalytic conversion. [ 111 ]…”
Section: C2n Applicationsmentioning
confidence: 99%
“…Notably, the binding energy of Co/FeÀ N increases from 398.92 to 399.72 eV, implying that the nitrogen in Co/FeÀ N serving as electron-rich donors can interact with lithium atoms in LiPSs molecules to form LiÀ N bond. [45] In the Li 1s spectrum (Figure 3d), the peak located at 55.48 eV is ascribed to the LiÀ S bond of Li 2 S 6 and a new characteristic peak at 56.34 eV is belonged to the LiÀ N bond. The XPS analysis suggests that Co/FeÀ N/MCFs have double-end binding sites towards LiPSs, which improve LiPSs trapping capacity.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, the N 1s peaks of Co/Fe−N/MCFs upshift to higher binding energies after treating with Li 2 S 6 solution (Figure 3c). Notably, the binding energy of Co/Fe−N increases from 398.92 to 399.72 eV, implying that the nitrogen in Co/Fe−N serving as electron‐rich donors can interact with lithium atoms in LiPSs molecules to form Li−N bond [45] . In the Li 1s spectrum (Figure 3d), the peak located at 55.48 eV is ascribed to the Li−S bond of Li 2 S 6 and a new characteristic peak at 56.34 eV is belonged to the Li−N bond.…”
Section: Resultsmentioning
confidence: 99%
“…All the samples demonstrated that more OCGs, especially –COOH, were introduced to the surface of AC. To further reveal the changes in OCGs on the supports before and after the ozone treatment, the Boehm titration method ( Appendix A ) [ 27 ] and XPS [ 28 , 29 ] analysis were exploited to investigate the property of the AC surface.…”
Section: Resultsmentioning
confidence: 99%